تحسين كفاءة الأبنية البيتونية المسلحة القائمة تحت تأثير الزلازل باستخدام أنظمة تدعيم مختلفة ومقارنتها مع بعضها باستخدام التحليل القائم على الأداء –دراسة حالة– - حسن, نايل محمد (Latakia University Journal -Engineering Sciences Series, 2018)
Many existing building in high seismic hazard zones (including buildings and structures in Syria) have inadequate capacity to resist earthquakes loads. This is because they may have been designed and constructed according to earlier codes, which did not satisfy modern seismic design requirements and current engineering standards, faulty design and improper construction, alteration of building functions, changes of seismic load characteristics in the area, etc.Syria code (as many international codes) adopted the conventional earthquake-resistant design philosophy (force based); the structures are designed for forces which are much less than the expected design earthquake forces. These methods usually don’t consider the expected performance level and seismic risk levels of the structure after an earthquake event. So need of new method comes which would give the actual performance of the structure after an earthquake event. Performance based analysis and evaluation procedures are used to investigate seismic inadequacy of existing buildings. The improvements of seismic performance of these buildings may be achieved using retrofit systems such as steel bracing, shearwalls, concrete and steel jacketing. In this paper, extensive literature study of most using retrofit schemes, which improve seismic performance of existing buildings, was introduced including their features. Procedures of performance based analysis using nonlinear static analysis (pushover) were used to study the performance of two local 4-story reinforced concrete existing buildings without/and with different retrofit systems. The seismic response and performance of these cases were discussed. The results of evaluation and analyses of 2-study cases showed necessity of3d- analysis, X-bracing is best system to bypass collapse plastic hinges and to reduce displacements and drifts, and concrete and steel jacketing bypass collapse hinges and keep ductility. تحسين كفاءة الأبنية البيتونية المسلحة القائمة تحت تأثير الزلازل باستخدام أنظمة تدعيم مختلفة ومقارنتها مع بعضها باستخدام التحليل القائم على الأداء –دراسة حالة– تعتبر العديد من المنشآت والمباني القائمة في المناطق ذات الخطر الزلزالي العالي (المباني والمنشآت في سوريا مثالاً) غير كافية في مقدرتها لمقاومة الحمولات الزلزالية. يعود ذلك إلى أسباب كثيرة منها أن هذه الأبنية صممت وأنشئت حسب الكودات الإنشائية في وقتها، وجود أخطاء في التصميم والتشييد غير الصحيح، تغيير وظائف البناء، تغيرات في خصائص الأحمال الزلزالية للمنطقة. اعتمد الكود السوري (مثل العديد من الكودات الأخرى) فلسفة التصميم التقليدية لمقاومة للزلازل (المعتمدة على القوة)، حيث يمكن أن تصمم المباني والمنشآت على قوى هي أقل من قوى الزلزال التصميمية المتوقعة. هذه الطرق عادة لا تأخذ في الاعتبار مستوى الأداء المتوقع ومستويات المخاطر الزلزالية للمنشأ بعد وقوع الزلزال. لذلك، تأتي الحاجة إلى طرق جديدة تعطي الأداء الفعلي للمنشأ بعد وقوع الزلزال وتستطيع تحقيق مستويات الأداء المطلوبة. تستخدم إجراءات التقييم والتحليل القائم على الأداء لتبيان العجز الزلزالي للمنشآت القائمة.يمكن رفع الكفاءة الإنشائية وتحسين الأداءالزلزالي لهذه الأبنية الضعيفة عن طريق تدعيمها أو تقويتها (إعادة تأهيلها إنشائياً) باستخدام تقنيات مختلفة مثل إضافة أربطة فولاذية، جدران بيتونية، قميص بيتوني وفولاذي. تم في هذا البحث تقديم دراسة مرجعية مكثفة لنظم التدعيم الأكثر استخداماُ لتحسين الكفاءة الإنشائية للأبنية القائمة، وتم تبيان خصائص كل منها كما تقديم نهج التحليل والتقييم القائم على الأداء باستخدام التحليل الستاتيكي اللاخطي من خلال دراسة حالة فراغية لبنائين قائمين مكونين من أربع طوابق تم تدعيمهما لتحسين الأداء الزلزالي لهما. أجريت 40 عملية تحليل، وتم مناقشة الأداء الزلزالي لاستجابة الأبنية لقائمة والمدعمة. بينت نتائج التحليل والتقييم للحالات المدروسة ضرورة التحليل الفراغي، وأن التربيط المعدني المتصالب X هو أفضل الحلول للتخلص من مفاصل الانهيار والتقليل من قيم الانتقالات لحد كبير (زيادة الصلابة الجانبية). وبينت النتائج أيضاً أن القميص البيتوني والجاكيت المعدني تتخلص من مفاصل الانهيار وتحافظ على المطاوعة.